Service Learning in Russia: Scoping Review - V. S. Nikolskiy (Высшее образование в России)
Over  the  past  few  years,  the  Service  Learning  approach  has  been  increasingly  introduced into the practice of Russian higher education institutions. Thereby researchers begin to take an active interest in this topic, and number of publications on service learning in the Russian context is growing. We are witnessing the emergence of a new area of educational research in our country. Under these circumstances, it is necessary to evaluate the successes in scientific knowledge, identify the existing gaps, and develop a programme for further research on service learning in our country. This circumstance determined the author’s interest in this topic and the choice of methodology in favour of a systematic review of the subject field. As a result, the author was able to identify an array of relevant publications, reconstruct the subject field, and identify seven main themes that have been covered  to  varying  degrees  in  the  literature:  1)  specificity  of  the  approach;  2)  civicism  formation; 3)  application  of  reflective  practices;  4)  use  of  an  evidence-based  approach;  5)  conceptualization; 6)  external  partners;  and  7)  the  role  of  the  teacher.  The  content  analysis  of  the  materials  made  it possible to identify the main characteristics of the publication array, identify lacunas and propose a programme of further research.